Use of the rice and corn husk ashes as an innovative pozzolanic material in ceramic tile adhesive production (2022)
In this study, the use of agro-industrial waste from rice and corn husk ashes as a pozzolanic addition for cement substitution in the manufacture of ceramic tile adhesive is presented. The cement replacement, at 15%, 20%, 25%, and 30%, shows good results, especially for the case of rice husk ash with an index of pozzolanic activity equal to 0,94. The physical-chemical treatment of the ashes is essential. In this case, it was carried out through a calcination process at 800°C and a subsequent grinding process. Test of consistency, open time, and adhesive resistance to traction, were carried out to evaluate the quality of the ceramic mortar.